Age-related differences and relationships between elements in human amygdala and other limbic system or basal ganglia - Yoshiyuki Tohno (2018)
To elucidate the compositional changes of the amygdala with aging, the authors investigated age-related differences of elements in human amygdalae. In addition, the relationships between the amygdala and other brain regions were investigated from a viewpoint of elements. After ordinary dissections at Nara Medical University were finished, the amygdalae were removed from the cerebra of the subjects who consisted of 22 men and 23 women, ranging in age from 70 to 101 years. In addition, the hippocampus, dentate gyrus, mammillary body of the limbic system and the caudate nucleus, putamen, and globus pallidus of the basal ganglia were also removed from the identical cerebra. After the brain samples were incinerated with nitric acid and perchloric acid, the element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that both the Ca and Mg contents increased significantly in the amygdalae with aging, but the other five element contents (P, S, Zn, Fe, and Na) did not change significantly in the amygdalae with aging. Regarding the relationships among elements, very significant or significant direct correlations were found among the Ca, P, and Mg contents in the amygdalae. To explore the relationships between the amygdala and either other limbic system or basal ganglia, the correlations between seven elements of the amygdala and hippocampus, dentate gyrus, or mammillary body, and between those of the amygdala and caudate nucleus, putamen, or globus pallidus which derived from the identical cerebra, were analyzed with Pearson's correlation. It was found that regarding the four elements of Ca, P, Mg, and Fe, a close relationship existed between the amygdala and hippocampus, globus pallidus, or mammillary body. © 2013 Springer Science+Business Media New York.